Cytotoxicity of separation orthodontic elastics Citotoxicidade de elásticos ortodônticos de separação - Rogério Lacerda dos Santos; Matheus Melo Pithon; Fernanda Otaviano Martins; Maria Teresa Villela Romanos (Dental Press Editora, 2012)
OBJECTIVE: To test the hypothesis that there is no difference in cytotoxicity between separating elastics of different manufacturers. METHODS: The present article compared latex elastics (4.0 mm, 4.4 mm and 4.8 mm) of four different manufacturers. The sample was allocated to seven groups of 9 elastics: Group A (American Orthodontics, green color, modules), Groups M1 and M2 (Morelli, blue color, modules and free in pack respectively), Groups M3 and M4 (Morelli, green color, modules and free in pack respectively), Group U (Uniden, blue color, free in pack) and Group T (Tecnident, blue color, free in pack) regarding their possible cytotoxic effects on oral tissues. Cytotoxicity assays were performed using cell culture medium containing epithelioid-type cells (Hep-2 line) derived from human laryngeal carcinoma and submitted to the methods for evaluating the cytotoxicity by the "dye-uptake" test, at time intervals 24, 48, 72 and 168 h. Data were compared by analysis of variance (ANOVA) and Tukey's test (p < 0.05). RESULTS: Results showed statistically significant difference (p < 0.05) between group U and all the other Groups (A, M1, M2, M3, M 4 and T) at 24 and 48 hours. CONCLUSIONS: Uniden elastics evoked more cell lysis at 24 and 48 h, although, all brands showed biocompatibility from 72 h onwards. OBJETIVO: o propósito do presente estudo foi testar a hipótese que não existe diferença de citotoxicidade entre elásticos de diferentes marcas. MÉTODOS: foram comparadas entre si 4 marcas de elásticos de separação (4,0mm, 4,4mm e 4,8mm) intrabucais de látex quanto ao possível efeito citotóxico nos tecidos bucais, divididos em 7 grupos de 9 elásticos cada: grupo A (cor verde - modular, American Orthodontics), grupos M1 e M2, (cor azul - modular e a granel, respectivamente, Morelli), grupos M3 e M4 (cor verde - modular e a granel, respectivamente, Morelli), grupo U (cor azul - a granel, Uniden) e grupo T (cor azul - a granel, Tecnident). O ensaio de citotoxicidade foi realizado utilizando-se cultura de células da linhagem HEp-2 (do tipo epitelióide, que tem origem em carcinoma de laringe humana), sendo submetido o material ao teste para células viáveis em vermelho neutro ("dye-uptake"), no tempo de 24, 48, 72 e 168 horas. A análise de variância e comparação múltipla (ANOVA) e o teste de Tukey foram utilizados (p<0,05). RESULTADOS: os resultados evidenciaram diferença estatisticamente significativa dos grupos A, M1, M2, M3, M4 e T com o grupo U nos tempos de 24 e 48h (p<0,05). CONCLUSÃO: pôde-se evidenciar que os elásticos da marca Uniden causaram alta quantidade de lise celular em 24 e 48h, porém, todas as marcas mostraram-se biocompatíveis a partir de 72h.